Fermentation Conditions that Affect Clavulanic Acid Production in Streptomyces clavuligerus: A Systematic Review - Ser, Hooi-Leng; Law, Jodi Woan-Fei; Chaiyakunapruk, Nathorn; Jacob, Sabrina Anne; Palanisamy, Uma Devi; Chan, Kok-Gan; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2016)
The β-lactamase inhibitor, clavulanic acid is frequently used in combination with β-lactam antibiotics to treat a wide spectrum of infectious diseases. Clavulanic acid prevents drug resistance by pathogens against these β-lactam antibiotics by preventing the degradation of the β-lactam ring, thus ensuring eradication of these harmful microorganisms from the host. This systematic review provides an overview on the fermentation conditions that affect the production of clavulanic acid in the firstly described producer, Streptomyces clavuligerus. A thorough search was conducted using predefined terms in several electronic databases (PubMed, Medline, ScienceDirect, EBSCO), from database inception to June 30th 2015. Studies must involve wild-type Streptomyces clavuligerus, and full texts needed to be available. A total of 29 eligible articles were identified. Based on the literature, several factors were identified that could affect the production of clavulanic acid in S. clavuligerus. The addition of glycerol or other vegetable oils (e.g. olive oil, corn oil) could potentially affect clavulanic acid production. Furthermore, some amino acids such as arginine and ornithine, could serve as potential precursors to increase clavulanic acid yield. The comparison of different fermentation systems revealed that fed-batch fermentation yields higher amounts of clavulanic acid as compared to batch fermentation, probably due to the maintenance of substrates and constant monitoring of certain entities (such as pH, oxygen availability, etc.). Overall, these findings provide vital knowledge and insight that could assist media optimization and fermentation design for clavulanic acid production in S. clavuligerus.